2021
DOI: 10.1080/19186444.2020.1768789
|View full text |Cite
|
Sign up to set email alerts
|

Financial stress index, growth and price stability in India: some recent evidence

Abstract: This paper examine aggregate financial stress index for India is constructed by taking monthly data from different segments of the financial market like money market, bond market, equity market, foreign exchange market, and the banking sector, for the period March 2007 to December 2016. The interrelationship and feedback effect between financial stress, economic growth and price stability are tested by using correlation and an unrestricted VAR model. The impulse response function of the VAR model shows that fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
3
4
0
1
Order By: Relevance
“…To achieve this purpose, the time-varying nature of the relationship between the price stability, financial stability, policy interest rate and money supply in the US, where monetary policies are designed to achieve price stability, full employment and moderate long-term interest rate targets, is studied econometrically with the TVP-SVAR model for the period 1993:12-2020:12. The results of the estimated TVP-SVAR models are parallel with the empirical findings of studies by Dhal et al (2011), Blot et al (2015), Sethi & Acharya (2020) and Sahoo (2020), who found mutual relationships between price and financial stability and who corroborate the proposition of the new environment hypothesis in the theoretical literature that price stability may not necessarily guarantee financial stability.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To achieve this purpose, the time-varying nature of the relationship between the price stability, financial stability, policy interest rate and money supply in the US, where monetary policies are designed to achieve price stability, full employment and moderate long-term interest rate targets, is studied econometrically with the TVP-SVAR model for the period 1993:12-2020:12. The results of the estimated TVP-SVAR models are parallel with the empirical findings of studies by Dhal et al (2011), Blot et al (2015), Sethi & Acharya (2020) and Sahoo (2020), who found mutual relationships between price and financial stability and who corroborate the proposition of the new environment hypothesis in the theoretical literature that price stability may not necessarily guarantee financial stability.…”
Section: Discussionsupporting
confidence: 83%
“…A study on Germany (Euro area) applied Bayesian VAR (Van Roye, 2011). In the context of India, the VEC (Ramesh Babu and Venkateswarlu, 2017) and VAR (Sahoo, 2020). Unsurprisingly, all these studies concluded that financial instabilities in the relevant countries negatively affect and prevent price stability.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The result, therefore, indicates that though the immediate impact of financial stress is not pronounced, it does have a negative future impact of output. is similar to the study of Sahoo (2020) in the case of India. In this study, it was revealed that financial stress does harm growth but with a certain time lag.…”
Section: Fsi and The Real Economysupporting
confidence: 84%
“…Sahoo (2020) utilized high frequency data from money market, bond market, equity market, foreign exchange market, and the banking sector in constructing a financial stress index for the Indian economy. Similar to the finding from Monin (2019), Sahoo (2020) found out that financial stress ensues in slowdown in economic growth and added that higher economic growth for a certain period of time gives rise in financial stress. Similarly, Ishrakieh et al (2020) implemented three market segments data from the Lebanese financial system in developing a financial stress index as a monitoring tool to maintain financial and economic stability in Lebanon.…”
Section: Literature Reviewsupporting
confidence: 84%